Effect of microwave rays on nymphs of Green Peach : ) (Homoptera1776(Sulzer)( Myzus persicae Aphids Aphididae) - A. Hadi, Forat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The research was conducted to study the effect of five exposure periods of microwave radiation (0,10,30,60 and 90) seconds on Nymph of the Green Peach Aphids Myzus persicae by counting the percentage of occured deformation ,rate of mortality percentage and emerged adults percentage, The study showed that the microwave radiation had a great effect on occurring deformation especially at the period 90 seconds, the exposure periods effect on the mortality percentage had a clear affect where the highest percentage of nymphs mortality was ( 52) for exposure period 90 seconds while it was found that the mortality was decreased to 48 and 24 for exposure periods 60 , 30 seconds which was significantly different in comparing with the control . The highest percentage of emerged adults was 92% at the exposure period 0 while the lowest percentage was 48 at the exposure period 90 seconds that caused a decrease of emerged adults .